2016
DOI: 10.1016/j.matdes.2016.05.066
|View full text |Cite
|
Sign up to set email alerts
|

Selective laser melting of AlSi10Mg: Influence of post-processing on the microstructural and tensile properties development

Abstract: Link to publication on Research at Birmingham portal General rights Unless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law. • Users may freely distribute the URL that is used to identify this publication. • Users may download and/or print one copy of the publication from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(111 citation statements)
references
References 25 publications
9
101
1
Order By: Relevance
“…Similar trends are shown in Zang et al [92]. For the additive processes, the fast cooling gradient associated with AM results in a very fine microstructure, which is very sensitive to the heat capacity data used and is characterized by columnar grains along the building direction and equiaxed grains in the cross section [93]. In the absence of large process-related defects, this microstructure is able to guarantee static properties and a hardness comparable and even higher than for a wrought material, even when heat treated [8,12], and can impede transgranular crack propagation.…”
Section: Microstructuresupporting
confidence: 80%
“…Similar trends are shown in Zang et al [92]. For the additive processes, the fast cooling gradient associated with AM results in a very fine microstructure, which is very sensitive to the heat capacity data used and is characterized by columnar grains along the building direction and equiaxed grains in the cross section [93]. In the absence of large process-related defects, this microstructure is able to guarantee static properties and a hardness comparable and even higher than for a wrought material, even when heat treated [8,12], and can impede transgranular crack propagation.…”
Section: Microstructuresupporting
confidence: 80%
“…To narrow the parameter field, experiments were carried out on a laser additive manufacturing system SLM Solutions SLM 125 HL. The system was built with a volume of 125 × 125 × 150 mm 3 and a Yb-fibre laser with a wavelength of 1070 nm and a maximum laser power of 400 W. The minimum focus diameter was 68 µm. The best results were obtained with a volume energy density of 61.7 J/mm 3 , a laser power of 370 W and a layer thickness of 50 µm.…”
Section: Laser Powder Bed Pusionmentioning
confidence: 99%
“…In comparison with conventional wrought alloys, hypoeutectic casting alloys have a poorer strength to ductility ratio. An AlSi10Mg alloy in as-built condition without heat treatment will achieve a tensile strength of about 400 MPa and a yield strength of about 300 MPa at a low elongation at break of about 5% [1][2][3]. These values are significantly above the characteristic values achieved by casting [4] and are the consequence of a completely different microstructure due to rapid solidification during additive manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…The quality and condition of the powder feedstock are other important factors controlling the final part quality. Tradowsky et al reported that samples prepared from recycled powder presented significantly more porosity than samples prepared from new powder . Indeed, it has been shown that moisture uptake by the powder may result in a significant increase in H 2 gas porosity in the fabricated part .…”
Section: Am Of Al Alloysmentioning
confidence: 99%